Exploring facilitators and barriers to introducing health technology assessment: a systematic review. (21st December 2022) - Suharlim, Christian; Kumar, Ritu; Salim, Julian; Mehra, Meenakshi; Gilmartin, Colin; Amaris Caruso, Ana; Castro, Hector
Abstract: Objective: This study aims to identify and codify the facilitators and barriers to help implementing partners institutionalize health technology assessment (HTA) successfully and navigate complex systems for health-related policy making. Methods: We searched for peer-reviewed and gray literature articles examining HTA programs globally using six databases. Keywords used as a guide for capturing articles included "health technology assessment, " "barrier, " and "facilitator" and their synonyms. Search results were scrutinized for duplicates and screened through a review of titles and abstracts. A full-text review was conducted exploring articles' coverage of twenty-seven evaluation criteria across four primary areas of interest: barriers/facilitators, motivations, guidelines, and institutional frameworks. Results: A total of 18, 599 records were identified for duplication check, title, and abstract review. A total of 1, 594 articles underwent full-text review, leading to a final synthesis of 262 studies. We found that ninety-seven articles discussed barriers/facilitators, with fifty-three of those discussing local capacity and unavailable human resources. Out of the sixty-six articles discussing motivations, forty-two cited the interest in supporting the decision-making process for, and promoting, appropriate resource allocation. Of the sixty-one articles that discussed guidelines and institutional framework, twenty-one articles described HTA as an independent national unit, and sixteen described their HTA unit as a unit within the Ministry of Health (MOH). Conclusions: This systematic review unpacks the dynamic and relevant contexts for understanding the HTA institutionalization process to help policy makers and practitioners achieve tangible progress in confronting the most critical issues facing priority setting and HTA institutionalization.